2015
DOI: 10.1186/s12913-015-0910-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of health worker performance after Integrated Management of Childhood Illness training in Benin: a cohort study

Abstract: BackgroundCorrect treatment of potentially life-threatening illnesses (PLTIs) in children under 5 years, such as malaria, pneumonia, and diarrhea, can substantially reduce mortality. The Integrated Management of Childhood Illness (IMCI) strategy has been shown to improve treatment of child illnesses, but multiple studies have shown that gaps in health worker performance remain after training. To better understand factors related to health worker performance, we analyzed 9,330 patient consultations in Benin fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
5

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 45 publications
3
25
5
Order By: Relevance
“…[41] Regarding IMCI training, many studies already reported its importance showing that those trained performed better than those who were not.. [42,43,44] So, building skills is crucial in IMCI strategy, both in terms of initial and continuing trainings. [44] The present study showed that less than two thirds of HCP received more than twice previous training in IMCI strategy. This implies that more efforts have to be directed towards providing continuous in-service IMCI training to improve their adherence.…”
Section: Discussionmentioning
confidence: 99%
“…[41] Regarding IMCI training, many studies already reported its importance showing that those trained performed better than those who were not.. [42,43,44] So, building skills is crucial in IMCI strategy, both in terms of initial and continuing trainings. [44] The present study showed that less than two thirds of HCP received more than twice previous training in IMCI strategy. This implies that more efforts have to be directed towards providing continuous in-service IMCI training to improve their adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Predictology as an important technical discipline, plays an increasingly important role in all walks of life today [20][21]. The 1990-2017 Health Human Resources Data are derived from the 2018 China Health Statistics Yearbook.More people/population ratio method, index smoothing method, gray prediction principle and method to predict the absolute demand of health manpower [22][23][24][25][26][27][28][29]. Kalman and Bucy began to study the uneven process of time series in the early 1960s, but did not form a certain system, prompting researchers to find ways to solve these problems [30][31].…”
Section: Methodsmentioning
confidence: 99%
“…e facility survey conducted in China showed that few sick children were fully assessed, and only 43.8% were correctly classified by health workers and the use of antibiotics for sick children was high and not according to guidelines [15]. According to the study conducted in Benin 63.6% children were treated in accordance with IMNCI guidelines and Performance of individual health workers varied greatly, from 15-88% of patients treated correctly, on average and also important performance gaps found immediately a er IMCI training persisted due to inadequate supervision and monitoring [10,21]. Similar study conducted in Kenya found that utilization and implementation of IMCI concepts in the region is approximately 14% which is below standard level established (above 68%), by WHO and UNICEF, due to recurrent staff deficit and also limited resource at disposal from the region [13].…”
Section: Imnci Implementation and Influencing Factorsmentioning
confidence: 98%
“…ese studies also mentioned a variety of factors that influences the implementation of the strategy by health workers. e most common identified problems are lack of training, poor supervision, lack of IMNCI essential drugs and on jobs aid, health workers perception, shortage of the staffs, nature of the strategy and lack of support from the government and stake holders [10][11][12][13][14][15][16][17][18][19][20][21]. Every day about 16,000 under five children continue to die in 2015, most of them will perish from preventable causes, such as pneumonia, diarrhea and malaria [22].…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation